Endoscopic retrograde cholangiopancreatography. Issue 6 (December 2014) - Singla, Sumit; Piraka, Cyrus; Talwalkar, Jay
<x xml:space="preserve">Abstract</x> Watch a video presentation of this article Answer questions and earn CME